2014
DOI: 10.1038/cddis.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent wrestling between detrimental and protective effects of H2O2 during myocardial ischemia/reperfusion

Abstract: Reactive oxygen species (ROS) and endoplasmic reticulum (ER) stress are paradoxically implicated in myocardial ischemia/reperfusion (I/R) injury and cardioprotection. However, the precise interpretation for the dual roles of ROS and its relationship with the ER stress during I/R remain elusive. Here we investigated the concentration-dependent effects of hydrogen peroxide (H2O2) preconditioning (PC) and postconditioning (PoC) on the ER stress and prosurvival reperfusion injury salvage kinase (RISK) activation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
0
30
0
2
Order By: Relevance
“…MDA malondialdehyde, GSH glutathione, SOD superoxide dismutase, GPx glutathione peroxidase Cell apoptosis/death-related tissue infarct and impaired cardiac functions are linked to oxidative stress in experimental I/R injuries [32]. Excessive generation of reactive oxygen species (ROS) during oxidative stress can initiate lipid peroxidation, oxidize proteins to inactive states, cause DNA damage and finally exacerbate I/R injury [17,33], and thus, timely elimination of excess ROS is thought to be beneficial. Since measures of ROS are difficult, the end products of free radical-mediated oxidative processes, such as MDA, are used to estimate ROS content [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA malondialdehyde, GSH glutathione, SOD superoxide dismutase, GPx glutathione peroxidase Cell apoptosis/death-related tissue infarct and impaired cardiac functions are linked to oxidative stress in experimental I/R injuries [32]. Excessive generation of reactive oxygen species (ROS) during oxidative stress can initiate lipid peroxidation, oxidize proteins to inactive states, cause DNA damage and finally exacerbate I/R injury [17,33], and thus, timely elimination of excess ROS is thought to be beneficial. Since measures of ROS are difficult, the end products of free radical-mediated oxidative processes, such as MDA, are used to estimate ROS content [34].…”
Section: Discussionmentioning
confidence: 99%
“…Since inflammation and oxidative stress are implicated in myocardial I/R injuries [16,17], the production of pro-inflammatory cytokines and oxidative stress-related factors was examined. We also investigated the potential regulatory mechanisms by which triptolide exerted its effects, with an emphasis on Nrf2/heme oxygenase-1 (HO-1) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Activation or overexpression of STAT3 greatly improves the myocardial survival after I/R injury through reducing oxidative stress [9], while the knockout of STAT3 or the inhibition of JAK2 by AG490 reverses the cardioprotection induced by IPoC [8,10]. However, it is unknown whether the enhanced ROS production during early reperfusion [4,5] activates STAT3 and thus contributes to the cardioprotection. Intracellular Ca 2+ overload is the second main contributor to myocardial I/R injury [1,11].…”
Section: Introductionmentioning
confidence: 96%
“…We recently found that IHH further increases the ROS production in cardiomyocytes during early reperfusion following ischemia [4]. This increase is required for a better postischemic contractile function and smaller infarct size through the effective activation of the reperfusion injury salvage kinases (RISKs) including protein kinase B (PKB/Akt) and protein kinase C epsilon (PKCε) [4,5]. However, it is unclear whether other signaling pathways are involved in the ROStriggered cardioprotection during the early reperfusion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation